ARIAS (assurance, relevance, interest, assessment, and satisfaction) learning model and learning interest: How does it affect critical thinking? - Wawan Wawan; Tubagus Pamungkas (Journal of Advanced Sciences and Mathematics Education, 2021)
This study aimed to determine whether 1) ARIAS learning model affected critical thinking skills; 2) students’ learning interest category (high, medium, and low) affected critical thinking skills; and 3) there is an interaction between the learning model groups and the learning interest groups on critical thinking skills. This research was a quasi-experimental research with a 2 X 3 factorial research design. The instruments used to collect the data were a critical thinking test and a learning interest questionnaire. The data analysis technique used in this research was the analysis of the two-way variance of two unequal cell paths. According to the results of research and discussion, it was found that 1) there was an effect of the ARIAS learning model on students’ critical thinking skills; 2) students’ learning interest did not affect their critical thinking skills; 3) there was no interaction between the ARIAS learning model and learning interest on critical thinking skills.